South Africa, race and the making of international relations - Thakur, Vineet (Kilombo (Series), 2020)
"This book offers readers an alternative history of the origins of the discipline of International Relations. Conventional, western histories of the discipline point to 1919 as the year of the 'birth of the discipline' with two seminal initiatives - setting up of the first Chair of IR at Aberystwyth and the founding of the Institute of International Relations on the side-lines of the Paris Peace Conference. From these events, International Relations is argued to have been established as a path to create peace in the post-War era and facilitated through a scientific study of international affairs. International Relations was therefore, both a field of study and knowledge production and a plan of action. This pathbreaking book challenges these claims by presenting an alternative narrative of International Relations. In this book, we make three interconnected arguments. First, we argue that the natal moment in the founding of IR is not World War I - as is generally believed - but the Second Anglo Boer War. Second, we argue that the ideas, methods and institutions that led to the making of IR were first thrashed out in South Africa - in Johannesburg, in fact. Finally, this South African genealogy of IR, we show in the book, allows us to properly investigate the emergence of academic IR at the interstices of race, Empire and science"--